2006
DOI: 10.1038/sj.ijir.3901496
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil dosed once a day in men with erectile dysfunction: a randomized, double-blind, placebo-controlled study in the US

Abstract: The efficacy and safety of tadalafil, dosed once a day for the treatment of erectile dysfunction, was assessed in a randomized, double-blind, placebo-controlled, parallel-design study at 15 US centers. Following a 4-week treatment-free run-in period, patients (X18 years of age) were randomly assigned to 24 weeks treatment with tadalafil 2.5 mg, tadalafil 5 mg or placebo. Primary efficacy endpoints were change at 24 weeks in International Index of Erectile Function Erectile Function (EF) Domain score and mean p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
99
5
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 24 publications
12
99
5
2
Order By: Relevance
“…There is also evidence confirming that tadalafil is efficacious when taken daily at doses of 2.5 and 5 mg. It was shown that daily use of 5-and 10-mg tadalafil for 12 weeks and daily use of 2.5-and 5-mg tadalafil for 24 weeks was well-tolerated and significantly improved erectile function (Porst et al, 2006;Rajfer et al, 2007), also in diabetic patients .…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…There is also evidence confirming that tadalafil is efficacious when taken daily at doses of 2.5 and 5 mg. It was shown that daily use of 5-and 10-mg tadalafil for 12 weeks and daily use of 2.5-and 5-mg tadalafil for 24 weeks was well-tolerated and significantly improved erectile function (Porst et al, 2006;Rajfer et al, 2007), also in diabetic patients .…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…Consistent with other studies, tadalafil significantly improved the EF and was generally well tolerated. 9,19,29 Unique end points included in this study were measures to evaluate the effect of treatment on participant's psychosocial outcomes and sexual satisfaction of participants and their partners, who were not directly treated.…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafil, which has longer half-life than other PDE5-Is, has been reported to have a time of action of up to 36 hours when taken at on-demand dosages and to be effective and safe in the treatment of ED when taken at once-daily dosages. 16 A clinical trial of patients with ED using a low dose of udenafil (25, 50, and 75 mg) once daily investigated the pharmacokinetic characteristics of udenafil and found that udenafil had a half-life of approximately 11 to 13 hours, its accumulation factor of maximum plasma concentration was 1.1 when consistently administered once daily, and its accumulation factor of trough plasma concentration was approximately 1.23 to 1.46, 4 leading to the marketing license of once-daily dosing of udenafil 50 mg in October 2010. 17 Subsequently, once-daily dosing of udenafil 50 and 75 mg was confirmed safe and effective in a clinical trial conducted for 24 weeks, 15 and this clinical trial was conducted to evaluate the long-term safety of udenafil 75 mg administered once daily for 24 weeks during this extension study.…”
Section: Discussionmentioning
confidence: 97%